Improving the nutritional quality of patients with edentulous totalis accompanied by severe lingir resorption using complete dentures: Meningkatkan kualitas gizi penderita edentulus totalis disertai resorbsi parah lingir menggunakan gigi tiruan lengkap - Tresnawati, Indah; Jubhari, Eri Hendra; Dammar, Irfan (Makassar Dental Journal PDGI Makassar, 2025)
Severe alveolar bone resorption is a challenge in the fabrication of complete dentures. Loss of all teeth often leads to impaired masticatory function, which can affect the digestive system and nutritional intake. The close mouth moulding technique is sug-gested to overcome the limitations of conventional techniques in flat ridge cases, in order to obtain a denture that is firm and comfortable to use, especially when chewing. This article describes the treatment of a flat ridge case in a patient with digestive and nutritional disorders, using the close mouth moulding technique. A 65-year-old woman came to RSGMP Unhas with com-plaints of loose dentures making it difficult to chew, and even had to undergo hospitalisation due to complaints of heartburn so that it was recommended to use a denture by an internal medicine doctor. The patient wanted to make a denture that was firm, comfortable, and improved his appearance. The patient was made an acrylic CD with a close mouth moulding technique. It was concluded that the close mouth moulding technique was effective in producing CDs that were firm, stable, and could restore masticatory function in patients with flat ridge.